PENGARUH PROGRAM KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP KEPUASAN KERJA PEGAWAI PADA PT. PLN (PERSERO) AREA PENGATURDISTRIBUSI MAKASSAR - Syafaruddin Syafaruddin; Amelia Resky Septiani Amin (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
AbstractThis study aims to partially analyze the influence of occupational health and occupational safety (K3) on the satisfaction of work care workers. The object of this research is employees at PT. PLN (Persero) Makassar Distribution Regulatory Area with a population of 56 employees who are also respondents in this study. The technique of collecting data is through questionnaires distributed to respondents, interviews and field observations. The research variables are occupational health and safety (K3) (X) and job satisfaction (Y). This study used descriptive analysis and simple regression analysis with quantitative approach, and to test its reliability level using Cronbach's Alpha. Hypothesis testing using Partial Test (T Test) with a significance level of 10%. Researchers used SPSS version 22.The results of this study stated that Occupational health and safety affects employee job satisfaction. Keywords: Theory of Human Resources, Occupational Health and Safety (K3), Job Satisfaction.